Albumin-bilirubin, Child-Pugh, and model for end-stage liver disease scores for the assessment of prognosis in cirrhotic patients - Jia Zhu; Xiaozhong Guo; Xingshun Qi (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Zhu J, Guo X, Qi X. Albumin-bilirubin, Child-Pugh, and model for end-stage liver disease scores for the assessment of prognosis in cirrhotic patients. Turk J Gastroenterol 2017.